Leveraging Parliamentary Friendship Groups to Strengthen Nigeria’s Strategic Alliances: A Foreign Policy Perspective - Ohiri, Chinasa Agatha; Nwali, Uche (Journal of Contemporary International Relations and Diplomacy, 2026)
This paper interrogates the underutilisation of Parliamentary Friendship Groups (PFGs) in advancing Nigeria’s strategic alliances in pursuit of its foreign policy objectives. Despite their growing global relevance as informal diplomatic channels, PFGs have had limited impact in the foreign policy space of African countries. In Nigeria, the full potential of PFGs for strategic partnerships is not being maximised. Extant literature identifies challenges limiting the impact of PFGs to include; underfunding, overlapping mandates, lack of continuity and insufficient integration of PFGs into the broader foreign policy framework. Beyond these, there are other challenges which have not received adequate scholarly attention. Amid the growing proliferation of PFGs, there is a dearth of national interest-driven PFGs and absence of tact in their inter-parliamentary engagements. The objective of this paper is to explore how these challenges are undermining the potential of Nigeria’s PFGs for strategic alliances. The study employed qualitative-descriptive method, relying on secondary data sources, including policy documents and scholarly literature. It adopted the soft power theory, which emphasises attraction, persuasion and informal influence over hard power in inter-state relations. It argues that PFGs, as a soft power instrument, could offer Nigeria a flexible and relational approach to international diplomacy, complementing formal channels and fostering mutual understanding in inter-state engagements. It recommends leveraging Nigeria’s PFGs as a deliberate tool of soft power diplomacy – aligned with national interest and embedded within foreign policy strategy. Additionally, there is a need for tact in the operations of Nigeria’s PFGs and capacity-building for legislators in inter-parliamentary diplomacy.